X 2 5x 4 x 2 3x 4
![x 2 5x 4 x 2 3x 4](https://prod-qna-question-images.s3.amazonaws.com/qna-images/question/5fa544c9-c440-4f94-850d-73173a8a80d4/e7e520db-51bb-4748-b635-0c0f9b532d14/7sthwa6.jpeg)
- 4x 4 5x 4 )/( x 2 3x 2
- 2 3x 2 5x x 4 )+ 4 x 1
- X 3 3x 2 5x 4 from 3x 3 x 2 2x 4
- X 4 3x 3 4x 2 5x 3 )/( x 2 x 4
- (- x 4 5x 2 3x 1 5x 4 3x 3 x 2 2x 3
- Lim x 2 5x 4 x 2 3x 4
- 4x 4 5x 4 )/( x 2 3x 2 long division
- Limx → − 4 x 2 5x 4 x 2 3x − 4
- F x )= 9x 2 5x 4 g x )=- 8x 2 3x 4
- F x )=- 5x 2 4x 9 g x )= 8x 2 3x 4
- 3 4 * x 2 5x 2 3x 2 1 4 * x 2
- Subtract x 3 3x 2 5x 4 from 3x 3 x 2 2x 4